Marketing intelligence & Planning. - Lim, Ming; Machado, Joana Cesar; Iglesias, Oriol (Emerald Group Publishing Limited, 2015)
The 8th Brand, Identity and Corporate Reputation Conference was held at the Universidade Católica Portuguesa (Porto) in the beautiful city of Oporto in April 2013, under the most able stewardship of the organizing chairs, Dr. Joana Machado and Dr. Leonor Carvalho, supported by the entire executive committee of the SIG. This ebook of carefully-selected chapters is the happy culmination of yet another successful conference, covering a broad, yet focused, range of issues in brand management today and providing truly international perspectives on brand consumption, B2B branding and consumer behavi.